Mekanisme Religio-Politik Pesantren: Mobilisasi Jaringan Hamida dalam Politik Elektoral Tasikmalaya - Hasanudin, Sansan (Masyarakat: Jurnal Sosiologi, 2017)
To be a winner in the electoral political contestation, the regional head candidates must have a strong political power. Thispolitical power could become from a variety of political machines, including boarding institutions (pesantren) which have a social network in the community. This article question is why boarding institutions or pesantren can be a mass base of electoral politics in an area and how the mechanism of involvement. The author used the concept of religio-political to see the involvement of pesantren in electoral politics and the concept of social networks as an analytical framework involvement mechanisms throughthe local elections in 2011 and 2016 in Tasikmalaya regency as a case study in which author sees the role of social networks pesantren as a political force. The author argues that the victory Uu Ruzhanul Ulum-Ade Sugianto in the elections of 2011 and 2016 is the result of the political power of social networking pesantren, namelyHimpunan Alumni Miftahul Huda (Hamida). The novelty of this article is that the political power could become from informal networks that integrated with formal network. This research data collection techniques are qualitative snowball-depth interview.